Analisa Pengaruh Customer Experience Terhadap Customer Satisfaction Pada Konsumen Di Rosetta's Cafe & Resto Surabaya - Roberto Gunawan Pranoto (Jurnal Strategi Pemasaran, 2015)
In the current era of globalization the success of a business required creative ideas from the businesses themselves. one of which is a culinary business. With the increasing growth of the effort restaurants and places to eat make business competition is tighter. Increasingly tight competition, the culinary businesses must create a customer experience that has dimensions of sense, feel, think, act, and relate that can make consumers feel happy and satisfied. This study aims to analyze the influence of Customer Experience of customer satisfaction to consumers in Rosetta's Cafe & Resto Surabaya. This study will be carried out by distributing questionnaires to 100 respondents consumers Rosetta's Cafe & Resto Surabaya. The analysis technique used is quantitative analysis with multiple linear regression method. Research proves that there is a significant influence of sense, feel, think, act, and relate to customer satisfaction in Rosetta's Cafe & Resto Surabaya.